KEPENTINGAN AUSTRALIA MELALUI HUBUNGAN DIPLOMATIK DENGAN INDONESIA DALAM PENYELESAIAN KONFLIK PAPUA - Geofany Dwiky Kurniawan; Ayu Sulistiarini; Arzidan Fadhlurrahman; Raihan Adrian Hermawan; Roy Setiawan (Jurnal Ilmiah Hubungan Internasional Fajar, 2026)
This journal aims to analyze Australia's interests through diplomatic relations with Indonesia in resolving the West Papua conflict. Using qualitative methods, this journal examines how Australia intervenes in human rights issues in Papua starting from the refugee case in 2006 which affected its diplomatic relations with Indonesia. The results of the discussion indicate that there are national interests that Australia wants to achieve in its intervention in the West Papua conflict. Australia applies quiet diplomacy in an effort to maintain diplomatic relations with Indonesia. At the same time, Australia also responds to domestic pressure on human rights violations in West Papua. Papua is also one of Australia's import sources for processed wood, oil, gas, fish and other marine animals which makes the Papua region economically important for Australia. Neorealism theory can be used to explain Australia's attitude as a strategy to fulfill its national interests amidst the tension of geopolitical dynamics. Keywords: Geopolitics, Indo-pacific, Interest, Human Rights, Bilateral